Exclusive Breast Feeding Management: Qualitative Study on Working Mothers in Kalibawang District, Kulon Progo Yogyakarta - Eva Putriningrum; Hermanu Joebagio; Eti Poncorini P (Journal of Health Policy and Management, 2016)
Background: Coverage of exclusive breastfeeding in Kalibawang, Kulon Progo, Yogyakartawas 688 in mothers (69.8%)in 2015, which mean did not reach intended target set by Health Ministry of 80%. One of the factors that can affect the failure of exclusive breast feeding is the flurry of mother andstart working. This study was aimed to investigate the exclusive breast feeding lactation management of qualitative study on working mother.Subject and Methods: This was a qualitative study, conducted in Yogyakarta, in July-September 2016. A total of 12 mothers with breast feeding and start working and 4 midwives who came from four Posyandu in Kalibawang. The data collected using the in-depth interviews, observation, document, and the data analyzed was using interactive analysis Miles and Huberman.Results: The result showed that knowledge management of lactation nursing mothers on mother and started working pretty well. Lactation management socialization barriers still prevailing lack of consciousness of mothers against the practice of lactation management because of lack of support from family, while the barriers experienced by mothers and started working in the lactation management do was the lack of opportunity is flushed and the unavailability of facilities in the workplace, as well as the existence of the syndrome of exclusive breastfeeding for less.Conclusion: the implementation of lactation management on mom and started the work influenced factor, there is cake and family support. Mothers tagline enhanced his motivation for coming to the meeting heldby the Clinics in order to be knowledgeable about lactation management can better yet so that the scope of exclusive breast feeding can match target. belonging to the Ministry of health.Keywords: lactation management, exclusive breastfeeding, working mothersCorrespondence: Eva Putriningrum. School of Health and Sciences, STIKes Jenderal Ahmad Yani, Yogyakarta.Journal of Health Policy and Management (2016), 1(1): 13-19https://doi.org/10.26911/thejhpm.2016.01.01.03